Pemberdayaan UMKM dalam Ekonomi Pembangunan Sebagai Solusi Pengurangan Kemiskinan dan Peningkatan Kesejahteraan - Ferdi Gunawan Siagian; Syahrinal Fajri; Mahesa Marpaung (STIKes Ibnu Sina Ajibarang, 2025)
This study uses a quantitative method to examine the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in the context of economic development, focusing on their role in poverty reduction and improving welfare. MSMEs play an essential role in creating jobs, alleviating poverty, and strengthening the economy, particularly in developing countries such as Indonesia. The study aims to analyze how MSME empowerment can reduce existing social and economic inequalities, while also contributing positively to the social welfare of communities. The main focus of this research is on empowerment programs implemented by both the government and the private sector, as well as the challenges and opportunities for MSME players across various sectors. Using primary and secondary data from 15 relevant journals, this study finds that better access to financing and appropriate training can increase MSMEs’ competitiveness, improving the welfare of micro and small business owners. The findings are expected to provide valuable insights for policymakers in formulating more effective MSME empowerment strategies.